Size and vegetation of urban parks in downtown San José, Costa Rica - Fallas Solano, Aarón (2018)
Worldwide, the natural landscape is being substituted by urban spaces, where green areas are basic for the conservation of many species. I analyzed size and vegetation in 15 urban parks of the Central San José, Costa Rica, in late 2009. Field work and municipal data shows that parks are small (1 786,82 to 21 220,94m2) and dominated by exotic species (87% of vegetation). Half the parks have an important component of 5m tall strata. Carmen district has tree lanes that act as corridors, an example that should be followed by other districts.